The importance of an interpreter's participation in a trial: theory and practice - Ibratova Feruza Babakulovna; Akramova Rano Azizovna (Zien Journals, 2024)
This article defines the role of the translator in the judicial process and the measures of his responsibility, and also analyzes the issues of court translators in Uzbekistan and compares them with the experience of foreign countries. It is concluded that competence, knowledge of legal vocabulary, knowledge of rights and obligations, as well as a high level of responsibility are the most important qualities that are required of such participants in legal proceedings
Keywords: translator; trial; competence; communication